2019
DOI: 10.1186/s13071-019-3501-0
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of continued Japanese encephalitis virus transmission in Singapore nearly three decades after end of pig farming

Abstract: Background Singapore used to report an annual average of 14 cases of Japanese encephalitis, but ever since the abolishment of pig farms in the early 1990s, the local incidence rate for Japanese encephalitis virus (JEV) infections has reduced drastically. Studies done in the early 2000s demonstrated the presence of JEV-specific antibodies in animals such as wild boars, dogs, chickens and goats on the offshore island and peripheral parts of the Singapore, indicative of prior JEV exposure. A JEV wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Japanese encephalitis is endemic in many Asian countries and contributes to an annual disease burden of *30,000-50,000 reported cases and 10,000 deaths (Solomon 2006, Erlanger et al 2009, Tiwari et al 2012. Subsequent to abolishment of pig farms in 1992, the incidence of Japanese encephalitis in Singapore dropped sharply (See et al 2002, Ting et al 2004, Koh et al 2006, Wang and Liang 2015, Yap et al 2019. However, serological surveys revealed exposure to Japanese encephalitis virus ( JEV) in wild boars, dogs, chickens, cows, and goats, suggesting the likelihood of an enzootic transmission cycle in local animal populations (See et al 2002, Ting et al 2004, Yap et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Japanese encephalitis is endemic in many Asian countries and contributes to an annual disease burden of *30,000-50,000 reported cases and 10,000 deaths (Solomon 2006, Erlanger et al 2009, Tiwari et al 2012. Subsequent to abolishment of pig farms in 1992, the incidence of Japanese encephalitis in Singapore dropped sharply (See et al 2002, Ting et al 2004, Koh et al 2006, Wang and Liang 2015, Yap et al 2019. However, serological surveys revealed exposure to Japanese encephalitis virus ( JEV) in wild boars, dogs, chickens, cows, and goats, suggesting the likelihood of an enzootic transmission cycle in local animal populations (See et al 2002, Ting et al 2004, Yap et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…However, seroprevalence of local wild pigs in Singapore remains relatively high at 15.2% for a country without recent clinical cases. From our study, it is shown that local birds have JEV seropositivity rate of 3.2% and the JEV antibody is detected mainly in herons and raptors [27]. This indicates possible sylvatic transmission between the vector and both the amplifying and reservoir hosts.…”
Section: Discussionmentioning
confidence: 60%
“…Further evidence of JEV seropositivity in ardeid birds, raptors, wild boars and sentinel chickens from 2010 till 2017 demonstrated that JEV transmission in animal hosts has continued despite the abolishment of pig farms [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Pigs act as an amplifier host of JEV, thus can be a key suspect of spreading infection to human living in close proximity [4]. The detection of JEV in pigs was reported earlier from Cambodia, Singapore, Vietnam, Australia, Japan, China, Thailand, Laos, Indonesia, India etc (Fig 6) [22, 34-42], however the studies on pigs for the presence of JE virus and its genotypes in circulation among pigs in India are limited [19]. Hence, the current investigation was mainly focused on the JE virus detection in pig serum and tonsil in three different JE endemic states of India namely Odisha, Assam and Manipur.…”
Section: Discussionmentioning
confidence: 95%